2018
DOI: 10.1097/aog.0000000000002637
|View full text |Cite
|
Sign up to set email alerts
|

Anhydramnios in the Setting of Renal Malformations

Abstract: Anhydramnios in the setting of severe malformations of the fetal kidney and urinary tract is associated with a high incidence of stillbirths and life-threatening complications, including severe pulmonary hypoplasia, umbilical cord compression, and perinatal asphyxia. To prevent such adverse outcomes, some centers in the United States and elsewhere are offering amniotic fluid restoration for women diagnosed with anhydramnios in the setting of fetal renal malformations. The procedures include infusions of amniot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…These programs also remain uninvestigated in large part. The growing interest in true investigation by the NICHD [15] and reputable perinatal centers is encouraging, and our hope is that it will be supported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These programs also remain uninvestigated in large part. The growing interest in true investigation by the NICHD [15] and reputable perinatal centers is encouraging, and our hope is that it will be supported.…”
Section: Discussionmentioning
confidence: 99%
“…A recent gathering of experts in the field provided opportunity for anecdotal reports of survival [18]. The conclusions of the symposium authors and others consider purposeful intervention in cases of BRA to be experimental, with performance occurring within the context of formal research studies [15, 18]. Currently, investigators in the North American Fetal Therapy Network collaborative have initiated a prospective study enrolling patients whose fetuses have BRA; however, this is specifically geared towards maternal safety of amnioinfusions and the ability to successfully perform neonatal dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…In August 2016, the National Institute of Diabetes and Digestive and Kidney Diseases and the Eunice Kennedy Shriver National Institute of Child Health and Human Development sponsored a workshop to define knowledge gaps related to anhydramnios secondary to severe congenital anomalies of the kidneys and urinary tract, including bilateral renal agenesis, and proposed a research agenda . In the absence of data to inform an evidence-based approach to prenatal management of anhydramnios, the workshop report concluded that hypotheses regarding the safety and efficacy of amnioinfusions should be tested in the setting of institutional review board (IRB)–approved research . The Renal Anhydramnios Fetal Therapy (RAFT) trial aimed to assess neonatal outcomes after serial amnioinfusions and to test the hypothesis that neonatal pulmonary survival without lethal pulmonary hypoplasia is possible after serial amnioinfusions in pregnancies complicated by anhydramnios from fetal anuria.…”
Section: Introductionmentioning
confidence: 99%
“…By 18 weeks of gestation, fetal urine becomes a major component of amniotic fluid, and the fetus begins to swallow amniotic fluid ( van Otterlo et al, 1977 ; Abramovich et al, 1979 ). Therefore, fetal renal/urinary system disorders are important causes of oligohydramnios in the second trimester, including intrinsic renal disorders (e.g., bilateral renal agenesis or renal tubular dysgenesis) and obstructive lesions of the lower urinary tract (e.g., posterior urethral valves and urethral atresia) ( Moxey-Mims and Raju, 2018 ). However, recurrent second-trimester oligohydramnios is a rare condition, and genetic etiology should be taken into consideration ( Shipp et al, 1996 ; Supplementary Table 1 ).…”
Section: Introductionmentioning
confidence: 99%